Direct-Triggering LTT With Monolithic Structure - Jinchao Yin; Yujie Bai; Kai Shi; Guipeng Liu; Ming Zhou; Jianhong Yang (IEEE Journal of the Electron Devices Society, 2022)
Light-triggered thyristor (LTT) has attracted considerable interest in power conversion and control systems because of its strong anti-interference ability and large power capacity. In this work, we propose a monolithic LTT that can be light-triggered directly without an amplifying gate (AG) design, to improve the device reliability and operating speed. The cathode structure is redesigned into an interdigitated structure with a relatively large light-incident area. The cathode shorts are re-arranged to balance the trigger intensity and the light incident depth, so as to ensure optimal $\text{d}{V}/\text{d}{t}$ capability. Devices are fabricated and adequate performances are obtained, verifying the feasibility of our design.